Consumerism and Rationality Against Cultural Influence - Sirajuddin, Sirajuddin; Nurmiati, Nurmiati (LAA MAISYIR : Jurnal Ekonomi Islam, 2021)
The culture of consumerism has expanded globally. Basically, this ideology is a derivative of investment capitalism which gives rise to a spirit of consumption with the aim of forming "self-identity". As a result, consumerism causes new problems in the order of life, namely psychological and manipulative damage, the formation of new social constructs, as well as economic inequality and ecological damage. This study aims to examine the assumptions in Islamic rasionality on the influence of consumerism. This research is a descriptive qualitative with systematic literature review(SLR) analysis tool to cary out studie, interpretations, extractions, and synthetic retrieval of previous studies. The results showed that the Islamic rationality described in the al-Qur’an is able to answer the problems caused by consumerism that occur. The assumptions in Islamic consumption that are interpreted in the Qur’an are: Consuming halal and thayyib and avoiding haram consumption; consumption is balanced simply and in moderation; consuming by prioritizing priority needs and social consumption; conduct sustainable and responsible consumption.